USING THE TPR (TOTAL PHYSICAL RESPONSE) GRAMMAR GAMES AT ENGLISH LESSONS - Berdaxova Shaxnoza Ajiniyaz qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article focuses on establishing the theoretical foundation that underpins the integration of Total Physical Response (TPR) grammar games into English language lessons. This chapter serves as the cornerstone for understanding the pedagogical rationale and principles guiding the utilization of TPR methodology in language instruction.